2021
DOI: 10.1002/bse.2850
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, social and governance disclosure and default risk

Abstract: We investigate whether environmental, social and governance (ESG) disclosure is related to default risk. Using a sample of US nonfinancial institutions from 2006 to 2017, we find that ESG disclosure is positively related to Merton's distance to default and is negatively related to the credit default swap spread, which suggests that firms with a higher ESG disclosure have lower default risk. Our analysis further indicates that the inverse effect of ESG disclosure on default risk is through increased profitabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 129 publications
(233 reference statements)
2
44
0
Order By: Relevance
“…Following prior studies (e.g., Atif & Ali, 2021; Cheng et al, 2014), we use Bloomberg's ESG score as an umbrella measure to assess the firm's ESG disclosure. ESG score ranges from 0.1 to 100, with high score indicating more transparency and disclosure.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following prior studies (e.g., Atif & Ali, 2021; Cheng et al, 2014), we use Bloomberg's ESG score as an umbrella measure to assess the firm's ESG disclosure. ESG score ranges from 0.1 to 100, with high score indicating more transparency and disclosure.…”
Section: Methodsmentioning
confidence: 99%
“…Following prior studies (e.g., Atif & Ali, 2021;Cheng et al, 2014) Bloomberg ESG data set that fail to provide information (E, S and G scores) on the three factors. We then employ the ESG index ranging from 0 to 1, based on the average extent to which ESG scores are disclosed.…”
Section: Measuring Esg Disclosure and Firm Life Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…Ratings disclosed by third-party ESG rating providers such as Bloomberg, MSCI and Refinitiv (formerly known as Thomson Reuters) are informative a Woei Chyuan Wong, Abd Halim Ahmad, Shamsul Bahrain Mohamed-Arshad, Sabariah Nordin & Azira Abdul Adzis as they provide objective evaluation of firm's ESG performance that is difficult for public to observe. Previous studies on ESG rating disclosures by third-party rating providers are found to improve firm's performance (Buchanan et al, 2018;Sahut & Pasquini-Descomps, 2015;Wong et al, 2021), reduce default risk (Atif & Ali, 2021) and financial risk (Lee & Faff, 2009;Oikonomou et al, 2012).…”
Section: Introductionmentioning
confidence: 97%